Etiology of Respiratory Distress in Newborn Experience in BIRDEM (BIRDEM Medical Journal, 2013)
Objectives: Respiratory distress is one of the most common causes of admission in Neonatal intensive care unit (NICU). There are many causes of respiratory distress, among them, transient tachypnoea of newborn, respiratory distress syndrome and perinatal asphyxia are commonest causes. The aim of this study was to identify the etiology of respiratory distress in special care baby unit (SCABU) in BIRDEM General Hospital and to observe the immediate hospital outcome of these babies. Methods: A retrospective study was conducted in SCABU, BIRDEM. Data were collected from all patients files admitted in to SCABU during the period from January to December 2011. Results: A total of 562 patients were admitted, among them 192 cases were admitted due to respiratory distress (34.1%). There was male predominance (64.6%). Two third (65.6%) babies were inborn and majority (84.4%) were born by caesarian section and preterm babies were more (65.6%). The commonest causes of respiratory distress in our study were transient tachypnea of newborn (43.2%), respiratory distress syndrome (30.2%), perinatal asphyxia (25%), septicaemia (16.1%) congenital pneumonia (11.9%), congenital heart disease (10.4%). All babies required oxygen initially, subsequently mechanical ventilation and Bubble CPAP was required in 48 (25.0%) and 8(04.1%) cases respectively. Mortality was 16.7% and was highest in neonates with respiratory distress syndrome (RDS) (71.8%) followed by septicaemia (40.6%) and perinatal asphyxia (37.3%). Among neonates requiring mechanical ventilation 56.2% died. Conclusion: Transient tachypnoea of newborn (TTN), respiratory distress syndrome (RDS), perinatal asphyxia and septicaemia were the common etiology for respiratory distress. Mortality was very high in RDS and septicaemia. Birdem Med J 2013; 3(1): 19-22 DOI: http://dx.doi.org/10.3329/birdem.v3i1.17122